Production Tracking and Managementfor SMEs - Dikky Setiawan; Denish M Chandra; Muhammad Saka Tauladani; Muhammad Al Faraby; Harnan Malik Abdullah (Eduvest - Journal of Universal Studies, 2021)
The problems experienced by Jazzy Souvenir SMEs are in the form of obstacles in monitoring the souvenir production process and difficulties in calculating the number of souvenirs that have been completed. The purpose of this study was to determine the method of designing PROTIM (Production Tracking and Management) as a monitoring system for the production process to increase production capacity in Jazzy Souvenir SMEs. This study uses qualitative methods with research in the form of program implementation. The implementation of the student creativity program in the field of science and technology application was carried out for three months which was divided into three stages, the first was problem identification and literature study at partner locations. The next stage is software design with the team using video conferencing. While the last stage is socialization, application of tools as well as monitoring and evaluation at SMEs Jazzy Souvenir. The conclusion that can be drawn from this research is that to overcome the obstacles in monitoring the souvenir production process as well as the difficulty in calculating the number of souvenirs that have been completed is to use the PROTIM design method (Production Tracking and Management) as a production process monitoring system to increase production capacity in MSME Jazzy Souvenirs. The existence of this innovation and new technology is very useful for partners in overcoming the problem of increasing production capacity for Jazzy Souvenir SME partner employees.